Pengaruh Penggunaan Game Edukasi Wordwall Tipe Open the Box Terhadap Hasil Belajar Kognitif IPAS Siswa di Sekolah Dasar - Yulistina Nur DS-; Tia Latifatusadiah; Hesti Widiastuti; Anggy Giri Prawiyogi; Meilani Amelia (Postgraduate, University of Mataram, 2024)
The purpose of this study was to determine whether there is an effect of using the open the box type wordwall educational game on the cognitive learning outcomes of IPAS students at SDN Palumbonsari 1, East Karawang District. This study used a quantitative method of pre-experiment type with a one group pretest posttest design. The population in this study were all fourth grade students of SDN Palumbonsari 1, totaling 135 people. The sampling technique used purposive sampling technique, so the sample in this study was class IV A with a total of 46 people. Data collection techniques using multiple choice tests as many as 30 items before and after treatment. Then carried out feasibility testing with validity test obtained 20 valid items, reliability test obtained r11 0.73, differentiator test and difficulty level. Data analysis techniques using descriptive statistical analysis and inferential statistics. Then the statistical hypothesis test was carried out with the paired sample t-test test obtained a Sig (2-tailed) value of 0.001 < 0.05, meaning that H0 was rejected and H1 was accepted. So it can be concluded that there is an effect of using the open the box type wordwall educational game on the cognitive learning outcomes of IPAS students at SDN Palumbonsari 1.